2018
DOI: 10.18632/oncotarget.24768
|View full text |Cite
|
Sign up to set email alerts
|

Blood free-circulating DNA testing by highly sensitive methylation assay to diagnose colorectal neoplasias

Abstract: Although methylated TWIST1 is a biomarker of colorectal neoplasia, its detection from serum samples is very difficult by conventional bisulfite-based methylation assays. Therefore, we have developed a new methylation assay that enables counting of even one copy of a methylated gene in a small DNA sample amount without DNA bisulfite treatment. We performed this study to evaluate the sensitivity and specificity of serum DNA testing by the new methylation assay in combination with and without the fecal immunochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 54 publications
0
25
0
1
Order By: Relevance
“…Thus, an increase in serum methylated SEPT9 may suggest the presence of other types of cancer. We have reported that serum methylated SEPT9 is significantly increased in patients with advanced colorectal adenoma and cancer . In the current study, colonoscopy was performed in all of the controls but not in all patients with CLD and with HCC, because it is difficult to perform a colonoscopy in patients who have no symptoms in relation to bowel movement.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Thus, an increase in serum methylated SEPT9 may suggest the presence of other types of cancer. We have reported that serum methylated SEPT9 is significantly increased in patients with advanced colorectal adenoma and cancer . In the current study, colonoscopy was performed in all of the controls but not in all patients with CLD and with HCC, because it is difficult to perform a colonoscopy in patients who have no symptoms in relation to bowel movement.…”
Section: Discussionmentioning
confidence: 80%
“…We have reported that serum methylated SEPT9 is significantly increased in patients with advanced colorectal adenoma and cancer. (17) In the current study, colonoscopy was performed in all of the controls but not in all patients with CLD and with HCC, because it is difficult to perform a colonoscopy in patients who have no symptoms in relation to bowel movement. We suggest that colonoscopy should be indicated for patients with CLD who have elevated methylated SEPT9 levels, to rule out colorectal neoplasms.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have created an analytically sensitive technique, the combined restriction digital PCR (CORD) assay, which is a very sensitive methylation assay allowing for the counting of as little as one copy of a methylated gene in a small sample of DNA without necessitating DNA bisulfite treatment. Its sensitivity for minute quantities of the target methylated gene is more than 100 times higher than that of conventional bisulfite-based methylation assays and thus overcomes the issue of limited sample input [12][13][14].…”
Section: Introductionmentioning
confidence: 99%